2011
DOI: 10.3109/02699052.2011.613090
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality-of-life and behavioural outcome in survivors of childhood meningitis

Abstract: Survivors with these sequelae should be screened for emotional and behavioural difficulties during key developmental transitions such as school entry. These findings strongly support recent UK clinical guidelines (NICE and SIGN) proposing that parents be made aware of possible psychological complications on discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Previous studies reported that ACNS’ survivors should be screened for emotional and behavioral difficulties, even if most patients fall within normal ranges on behavioral measures [ 8 ]. Identifying internalizing disorders may predict the risk of anxiety disorders in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that ACNS’ survivors should be screened for emotional and behavioral difficulties, even if most patients fall within normal ranges on behavioral measures [ 8 ]. Identifying internalizing disorders may predict the risk of anxiety disorders in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 17 full-text articles on which data extraction was performed (see Table 1), 4 dealt with anogenital warts [15][16][17][18], 3 with influenza [19][20][21], and 5 with the impact of meningitis, though these are classified in Table 1 according to the causative agents, which included Haemophilus influenzae type B [22], meningococcal meningitis [23], bacterial meningitis in general [22,24], and pneumococcal disease [25,26]. Of the studies dealing with bacterial meningitis in general, one dealt with pneumococcal and bacterial meningitis but excluded that caused by H. influenzae type B [24] and the other dealt with bacterial meningitis caused by any of the three pathogens mentioned [22]. In addition, we found four studies in rotavirus [27][28][29][30] and one in patients with varicella [31].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with meningitis, interestingly, had higher MCS-12 scores. This was unexpected, as one would expect a central nervous system infection to negatively impact psychological outcomes [ 12 ]. However, it is possible that meningitis, which may not require surgery or as long of an OPAT course and may have been due to conditions such as neuroborrelliosis or neurosyphilis, has lower cumulative impacts on patients.…”
Section: Discussionmentioning
confidence: 99%